Covid-19 and E-wallet usage intention in Kyrgyzstan - Yong, Wooi Keong *; Maizaitulaidawati, Md. Husin; Zhamgyrchiev, Nurusultan (Asian Journal of Humanities and Social Studies, 2023)
The usage of electronic commerce has continued to expand since the Covid-19 pandemic began in developed and developing countries. However, the usage of electronic commerce in Central Asian countries is underresearched. This study aims to determine the factors that influence e-wallet usage intention in Kyrgyzstan. The theory of planned behaviour (TPB) is extended and adopted in developing the hypotheses. Using surveys, 319 questionnaires were collected from young and middle-aged adults in Kyrgyzstan. The findings show that attitude, subjective norm and perceived behavioral control has a positive relationship with intention to use e-wallets. It is also found that attitude and intention will be stronger if the perceived behavioral control is high. The findings suggest ways to enhance the use of e-wallets in in Kyrgyzstan.